Opioid Use Disorder and Employee Work Presenteeism, Absences, and Health Care Costs. Issue 5 (May 2020) - Henke, Rachel Mosher; Ellsworth, David; Wier, Lauren; Snowdon, Jane
Abstract : Objective: To measure the prevalence of opioid use disorder (OUD) and employee health care and productivity costs with and without OUD and to assess whether utilization of pharmacotherapy for OUD reduces those costs. Methods: We conducted a cross-sectional analysis of 2016 to 2017 commercial enrollment, health care, and pharmacy claims and health risk assessment data using the IBM ® MarketScan ® Databases (Ann Arbor, MI). We estimated regression models to assess the association between OUD and annual employee health care and productivity costs. Results: Health care and productivity costs for employees with OUD who did and did not receive pharmacotherapy were approximately 6294 and 21, 570 more than for other employees, respectively. Conclusions: Employers can make a business case for expanding access to pharmacotherapy treatment for OUD based on our finding that receipt of pharmacotherapy significantly reduces overall health care costs. Abstract : Supplemental Digital Content is available in the text